2005
DOI: 10.1158/0008-5472.can-04-1911
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic K-RAS Is Required to Maintain Changes in Cytoskeletal Organization, Adhesion, and Motility in Colon Cancer Cells

Abstract: RAS oncogenes are thought to play a role at multiple stages of tumorigenesis. The role and mechanisms by which RAS oncogenes maintain the transformed state of human cancer cells are poorly understood. Here, we have studied the role of oncogenic K-RAS in maintaining cytoskeletal disruption, cell adhesion and motility in metastatic colon carcinoma cells. Targeted deletion of K-RAS G13D from HCT116 colon carcinoma cells restored their ability to assemble stress fibers and focal adhesions/complexes, accompanied by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
108
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(125 citation statements)
references
References 44 publications
17
108
0
Order By: Relevance
“…Indeed, expression of KrasV12 also increased the mechanical deformability of non-tumorigenic cells ( Figure 5D and Table 1). Similarly, knockout of a mutant Kras allele in colon tumor cells increased pMLC2 levels ( Figure 5E), as previously reported [20], and converted these mutant Kras-knockout cells into losers over their tumorigenic counterparts ( Figure 5F). Together, these data demonstrate that the activation of Kras influences entosis by inducing winner status.…”
Section: Oncogenic Kras Imparts Winner Status To Cellssupporting
confidence: 85%
“…Indeed, expression of KrasV12 also increased the mechanical deformability of non-tumorigenic cells ( Figure 5D and Table 1). Similarly, knockout of a mutant Kras allele in colon tumor cells increased pMLC2 levels ( Figure 5E), as previously reported [20], and converted these mutant Kras-knockout cells into losers over their tumorigenic counterparts ( Figure 5F). Together, these data demonstrate that the activation of Kras influences entosis by inducing winner status.…”
Section: Oncogenic Kras Imparts Winner Status To Cellssupporting
confidence: 85%
“…However, TBP-1 immunoprecipitates contained Fra-1 species of differing mobilities on SDS-polyacrylamide gel electrophoresis gels, a likely indication that multiple phosphorylation states of the protein were present . In KRAS mutant HCT116 colon carcinoma cells, which express high levels of endogenous Fra-1 (Pollock et al, 2005), we found that endogenous TBP-1 was present in immunoprecipitates prepared using anti-Fra-1 but not control (IgG) antibodies (Figure 2b), and that only a small proportion of the TBP-1 in these cells was associated with Fra-1. In contrast to Fra-1, we found that c-Fos did not associate with TBP-1 in HEK293 cells (Figure 2c), indicating the capacity to interact with TBP-1 was not a property shared by all Fos family members.…”
Section: Resultsmentioning
confidence: 95%
“…Overexpression of the Fra-1 transcription factor in human cancers is strongly linked to tumour growth, migration and invasion Belguise et al, 2005;Debinski and Gibo, 2005;Pollock et al, 2005;Young and Colburn, 2006;Adiseshaiah et al, 2007;Doehn et al, 2009;Luo et al, 2010). Understanding the mechanisms regulating Fra-1 accumulation in tumour cells is a key issue, but one that is not fully understood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In breast and colon carcinoma-or in glioblastoma-derived cell lines, Fra-1 knockdown resulted in prominent alterations in cell morphology and it altered the configuration and the distribution of actin filaments Belguise et al, 2005;Pollock et al, 2005;Debinski and Gibo, 2005). Fra-1 counteracted stress fibre formation by either reducing RhoA activity or interfering with this pathway downstream of Rho (Pollock et al, 2005), resulting in increased cell motility and decreased adhesion.…”
Section: Introductionmentioning
confidence: 99%